Penguasaan kosa kata dan kemampuan membina ayat bahasa Thai - Che Su, Norizan; Zainon Hamzah, Zaitul Azma (Persatuan Linguistik Malaysia, 2013)
This study was conducted to identify the vocabulary mastery and ability to construct sentences Thai language by students of Universiti Putra Malaysia (UPM). A total of 41 students who attended the Thai Language Proficiency Course Level One has been selected as the sample using purposive sampling technique. A research tool BBT Final Exam questions (Part III and Part IV). Data were analyzed using error analysis approach. The study found that students can master the vocabulary and can construct Thai sentences using correct grammar structure. In addition, the structure of the first language students also affects language-learning Thai as a foreign language at the Universiti Putra Malaysia.